2015
DOI: 10.1185/03007995.2015.1085849
|View full text |Cite
|
Sign up to set email alerts
|

Practical guidance for dosing and switching from paliperidone palmitate 1 monthly to 3 monthly formulation in schizophrenia

Abstract: ClinicalTrials.gov identifier: NCT01559272 and NCT01529515.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…The first paper reported the results of a Phase 1, single dose, randomized, open label study conducted to investigate the PK, safety, and tolerability of PP-3M in patients with schizophrenia, 25 the second paper focused on the efficacy and safety of PP-3M emerging from a four phase RCT 26 ( Table 1 ), whilst the third related to practical issues implicated in the dosing and switching from PP-1M to PP-3M. 27 Of the five posters retrieved, two 28 , 29 reported data from the randomized clinical trials more extensively described in a paper by Berwaerts et al; 26 the others 30 – 32 reported data more extensively described in a paper by Ravenstijn et al 25 For the purpose of the present review, the main findings relating to the formulation, pharmacodynamics and PK, safety, tolerability, and efficacy of PP-3M will be described, followed by the presentation of practical issues encountered while using this new formulation. The review will conclude with considerations of the position occupied by PPM-3M in the current therapeutic scenario.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first paper reported the results of a Phase 1, single dose, randomized, open label study conducted to investigate the PK, safety, and tolerability of PP-3M in patients with schizophrenia, 25 the second paper focused on the efficacy and safety of PP-3M emerging from a four phase RCT 26 ( Table 1 ), whilst the third related to practical issues implicated in the dosing and switching from PP-1M to PP-3M. 27 Of the five posters retrieved, two 28 , 29 reported data from the randomized clinical trials more extensively described in a paper by Berwaerts et al; 26 the others 30 – 32 reported data more extensively described in a paper by Ravenstijn et al 25 For the purpose of the present review, the main findings relating to the formulation, pharmacodynamics and PK, safety, tolerability, and efficacy of PP-3M will be described, followed by the presentation of practical issues encountered while using this new formulation. The review will conclude with considerations of the position occupied by PPM-3M in the current therapeutic scenario.…”
Section: Resultsmentioning
confidence: 99%
“…Based on published studies, Gopal et al 27 have provided guidance for the practical use of PP-3M. In particular, switching to PP-3M is only recommended in patients who have previously been treated with PP-1M for at least 4 months; the first injection should be given at the time of the first scheduled administration of PP-1M, with a dosing window of ±1 week.…”
Section: Practical Issues For Dosing and Switchingmentioning
confidence: 99%
“…These tiny drug crystals are dispersed in an aqueous suspension (nanosuspensions), which is the LAI formulation of PP. 72 The PP3M formulation utilizes Nano-Crystal technology similar to the PP1M but with increased particle size, allowing an extended sustained release. 59 These nanoparticles dissolve slowly after intramuscular (IM) injection before being hydrolyzed to paliperidone by the esterases present in muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Then paliperidone diffuses into the systemic circulation. 72 , 73 PP3M is available in dose strengths of 273, 410, 546 and 819 mg paliperidone palmitate that undergo hydrolysis, resulting in dose strengths of 175, 263, 350 and 525 mg of paliperidone, respectively. 72 …”
Section: Discussionmentioning
confidence: 99%
“…Intention-to treat analyses were used, where appropriate. Equivalent doses were determined through published tables of chlorpromazine equivalents (Andreasen et al, 2010), or in the case of paliperidone 3-monthly through published guidelines (Gopal et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%